Comparison of Long-Term Survival Outcomes of T4a and T4b Colorectal Cancer - Lim, Ji Ha; Huh, Jung Wook; Lee, Woo Yong; Yun, Seong Hyeon; Kim, Hee Cheol; Cho, Yong Beom; Park, Yoon Ah; Shin, Jung Kyong (Frontiers in Oncology, 2022)
Background: Although T4b is known to have worse oncologic outcomes, it is unclear whether it truly shows a worse prognosis. This study aims to compare the survival differences between T4a and T4b. Methods: Patients who were pathologically diagnosed with T3 and T4 colorectal adenocarcinoma from 2010 to 2014 were included (T3, n = 1822; T4a, n = 424; T4b, n = 67). Overall survival (OS) and cancer-specific survival (CSS) were compared between T4a and T4b using the Kaplan-Meier method and log-rank test. Results: In stage II, T4a had better OS and CSS than T4b (5-year OS, 89.5% vs. 72.6%; 5-year CSS, 94.4% vs. 81.7%, all p < 0.05), however, in stage III, there were no significant differences in survivals between groups (all p > 0.05). In multivariable analysis, T classification was not an independent risk factor for OS (p > 0.05). However, for CSS, when respectively compared to T3, T4b (HR 3.53, p < 0.001) showed a relatively higher hazard ratio than T4a (HR 2.27, p < 0.001). Conclusions: T4a showed more favorable OS and CSS than T4b, especially in stage II. Our findings support the current AJCC guidelines, in which T4b is presented as a more advanced stage than T4a.